Cloning, characterization and expression of the gene that encodes the major neutralization-specific antigen of African horsesickness virus serotype 3 - Huismans, H. (Henk), 1942- (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2010.